Liquid-vapor phase diagram of carbon dioxide near the critical point - Azzedine Abbaci (The Journal of Engineering and Exact Sciences)
Reliable information on the properties of supercritical fluids is sought due to their importance in chemical technology. For this purpose, we consider the crossover model to explain the behavior of the thermodynamic properties of fluids in the vicinity of the critical point. In particular, we present an up-to-date examination of the coexistence densities of carbon dioxide near the critical point and compare it the experimental data of Duschek et al. as well as with the data generated from NIST REFPROP package.